Diagnostic Value of Positron Emission Tomography Combined with Computed Tomography for Evaluating Critically Ill Neurological Patients - Kampe, Knut Kurt William; Rotermund, Roman; Tienken, Milena; Thomalla, Götz; Regier, Marc; Klutmann, Susanne; Kluge, Stefan (Frontiers in Neurology, 2017)
Purpose: 18F-fluorodeoxyglucose positron emission tomography combined with computed tomography (FDG-PET/CT) is a promising new tool for the identification of inflammatory, infectious and neoplastic foci. The aim of our work was to evaluate the diagnostic value of FDG-PET/CT in patients treated on a neurological / neurosurgical ICU or stroke unit. Methods: We performed a single-center, 10-year, retrospective evaluation of the value of FDG-PET/CT in critically ill adult patients with severe neurological disease. Results: 42 patients underwent FDG-PET/CT. Of these, 15 were ventilated and 10 were under vasopressor support. We identified four indications for performing FDG-PET/CT: 1) excluding a paraneoplastic etiology in an otherwise unexplained encephalitis, encephalopathy or neuropathy, 2) detecting a large vessel vasculitis in patients with ischemic stroke, 3) detecting an infectious focus in sepsis, and less frequently 4) evaluating cerebral metabolism. In 22 patients evaluated for an unknown malignancy, five scans revealed either a previously unknown tumor or unknown metastases of a previously treated malignancy. Of 11 patients investigated for large vessel vasculitis, two showed an inflammation of arteries supplying the brain. Of 6 sepsis cases, FDG-PET/CT identified an infectious focus in 4. Summary: We found FDG-PET/CT to be a helpful tool in critically ill neurological patients. The results of the FDG-PET/CT had direct therapeutic consequences in the 12 true-positive cases. In 24 of the 29 negative cases, FDG-PET/CT helped exclude alternative diagnoses and/or influenced therapy. Our findings demonstrate the feasibility and diagnostic benefit of FDG-PET/CT in this group of patients.